Effects of Aging on the Neural Mechanisms Underlying the Recollection of Memories Encoded by Social Interactions With Persons in the Same and Different Age Groups - Tsuruha, Eri; Tsukiura, Takashi (Frontiers in Behavioral Neuroscience, 2021)
Memories related to ingroup members are remembered more accurately than those related to outgroup members. However, little is known about the age-dependent differences in neural mechanisms underlying the retrieval of memories shared with ingroup or outgroup members that are categorized by age-group membership. The present functional magnetic resonance imaging (fMRI) study investigated this issue. Healthy young and older adults participated in a 2-day experiment. On the first day outside fMRI, participants were presented with words by unfamiliar persons in movie clips and exchanged each word with persons belonging to the same age group (SAG) or different age group (DAG). On the second day during fMRI, participants were randomly presented with learned and new words one by one, and they judged whether each word had been encoded with either SAG or DAG members or neither. fMRI results demonstrated that an age-dependent decrease in successful retrieval activation of memories presented by DAG was identified in the anterior temporal lobe (ATL) and hippocampus, whereas with memories presented by SAG, an age-dependent decrease in activation was not found in any regions. In addition, an age-dependent decrease in functional connectivity was significant between the hippocampus/ATL and posterior superior temporal sulcus (pSTS) during the successful retrieval of memories encoded with the DAG people. The “other”-related mechanisms including the hippocampus, ATL, and pSTS with memories learned with the outgroup members could decrease in older adults, whereas with memories learned with the ingroup members, the “self”-related mechanisms could be relatively preserved in older adults.